2018
DOI: 10.1002/1878-0261.12376
|View full text |Cite
|
Sign up to set email alerts
|

miR‐372 and miR‐373 enhance the stemness of colorectal cancer cells by repressing differentiation signaling pathways

Abstract: miR‐372/373, a cluster of stem cell‐specific microRNAs transactivated by the Wnt pathway, has been reported to be dysregulated in various cancers, particularly colorectal cancer (CRC); however, the unique role of these microRNAs in cancer remains to be discovered. In the present study, we characterized the upregulation in expression of miR‐372/373 in CRC tissues from The Cancer Genome Atlas data, and then showed that overexpression of miR‐372/373 enhanced the stemness of CRC cells by enriching the CD26/CD24‐po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 69 publications
1
54
0
Order By: Relevance
“…This study further identifies that ZBTB7A is also under the post-transcriptional control of miR-372 in addition to there being gene copy loss during oral tumorigenesis. Since miR-372 is a prognostic determinant of a wide panel of malignancies (8,11,13), the miR-372-ZBTB7A axis would seem likely to be a therapeutic target when treating such malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study further identifies that ZBTB7A is also under the post-transcriptional control of miR-372 in addition to there being gene copy loss during oral tumorigenesis. Since miR-372 is a prognostic determinant of a wide panel of malignancies (8,11,13), the miR-372-ZBTB7A axis would seem likely to be a therapeutic target when treating such malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the EMT is highly associated with drug resistance (58), it is likely that the ZBTB7A-TRAIL-R2 axis may also attenuate EMTassociated drug resistance. Since disruptions of the miR-371-miR-373 cluster and the chromosome 19q13 locus are rather common in malignancies (4,6,8,10,(12)(13)(14), genome-wide studies should help with a more comprehensive understanding of how aberrations in the miR-372-ZBTB7A-TRAIL-R2 cascade affect oncogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNA-215 DTL [59] miR-148a WNT, β-catenin [60] miR-199a/b Gsk3β, Wnt/β-catenin-ABCG2 [61] miR-196b-5p STAT3 [62] miRs-31 EphB2 and EphA2 [63] miR-27a Apaf-1/caspase-9 [64] miR-372/373 Nanog, Hedgehog, NFκB, MAPK/Erk, VDR Jak-STAT, TGF-beta, PI3K-Akt, MAPK. [65,66] miR-137 DCLK1 [67] miR-146a β-catenin [68] miR-195-5p STAT3, BIRC5, BCL2, BCL-XL, SOX2, CD133, RBPJ, Notch2 [62,69] Lung miR-128 AKT/ERK, p38, c-met/PI3K/AKT, VEGF/PI3K/AKT, IL-6-JAK-STAT3 [70][71][72][73] miR-181b Notch2 [74] miR-138 TGFβ [75] miR-5100 Rab6 [76] miR-214 c-MYC [76] miR-708-5p Wnt/β-catenin [77] miR-873 miR-125a-3p…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…They demonstrated that the upregulated expression of miR-372/373 enhanced CSC features via enrichment of stem-cell-positive cells ultimately responsible for chemoresistance, self-renewal, and metastasis of CRCs. Further, they also elucidated the underlying mechanism of miR-372/373-induced stemness and revealed that activated Nanog and Hedgehog signaling pathways are critically associated with the development and function of stem cells while the functioning of NFκB, mitogen-activated protein kinase (MAPK)/Erk, and VDR signaling mechanisms vital for differentiation was inhibited by miR-372/373, which suggests that miR-372/373 upregulates CRC stemness features via acting on various signaling mechanisms associated with the regulation of stemness and differentiation [65].…”
Section: Colorectal Cancermentioning
confidence: 99%